THAILAND PORT THROUGHPUT PREDICTION VIA PARTICLE SWARM OPTIMIZATION BASED NEURAL NETWORK - Kunnapapdeelert, Siwaporn; Thepmongkorn, Sirinthorn (Journal of Applied Engineering Science, 2020)
Shipping volume in Thailand have significantly increased in last four years. It is important to pay attention to the trend of Thailand port throughput and use as the guideline to prepare for the needs of supporting facilities, infrastructures, financial and human resources. An effective forecasting technique called particle swarm based neural network (PSONN) is developed to estimate Thailand port throughput in this work. The prediction results from PSONN and classical backpropagation training algorithm, backpropagation neural networks (BPNN) were compared. The results shown that PSONN provides more accurate results than BPNN when apply to predict port throughput of Thailand. The mean squared error obtained from PSONN are about 10 times lower than that of BPNN. This confirms that neural network based on PSO training algorithm has better performance and better ability to escape local optimum than that of BPNN.